Prevalence and Predictors of Missed Nursing Care in Intensive Care Units: A Multicentre Cross‐Sectional Survey - Suqin Xiao; Rong Jiang; Qin Xiong; Yang Yang; Hui Hong; Lingpeng Tang; Jie Zhang; Hongsuo Liu (Nursing in Critical Care, 2026)
ABSTRACT Background Missed nursing care (MNC) in intensive care units (ICUs) is associated with adverse patient outcomes, yet multicentre evidence from mainland China remains limited. Aim To describe the level and pattern of MNC among ICU nurses in China and to identify associated factors. Study Design Multicentre cross‐sectional survey across China. Results Of the 900 questionnaires distributed, 840 valid responses were included in the final analysis. The mean total MNC score was 98.9 ± 22.4. Psychological support, basic nursing care and rehabilitation care were the most frequently missed domains. The mean score for perceived causes of MNC was 72.3 ± 15.8, with absolute and relative shortages of human resources and communication‐related factors identified as the leading contributors. Average number of patients cared for per shift, ICU specialist nurse qualification, professional title and hospital level were significantly associated with total MNC score, together explaining 24.4% of the variance. Conclusions MNC is common in Chinese ICUs, particularly in psychosocial, basic and rehabilitation‐related care. Organisational context, nurse workload and professional preparation appear to be important factors associated with MNC. Targeted strategies are needed to optimise staffing, strengthen specialist training and improve communication processes in ICU teams. Relevance to Clinical Practice Better understanding of the pattern and key associated factors of MNC may help nurse managers prioritise staffing, competency development and communication improvement to enhance ICU nursing quality and patient safety.